Species complexes: confusion in identifying the true vectors of malaria and other parasites - Paskewitz, Susan (Henry Stewart Talks, 2010)
History and the anopheline mosquito species complexes, Methods of identification of species complexes (behavioral, genetic, chromosomal), Molecular tools for diagnosis of species, Evolution of species complexes, Ecological and ecotypic speciation
Archived at 2021/02/25